The only basic Project: Teaching basic operations with fractions in pandemics times (Research, Society and Development, 2021)
This article has the intention of presenting the Project developed at the EEEP Antônio Valmir da Silva school relevant content of operations with fractions, in addition to providing greater interactivity between students, the teacher and content. The project Só o Básico develops, through activity proposals, allied to technologies, a different way that uses teaching methodology through comics. The project " Only the Basic" develops, through activity proposals, allied to technologies, a different way that uses teaching methodology through comics. Educational comics aim to overcome the difficulties that students have in basic operations with fractions.These metodology applied with comics are necessary so that students can not only succeed in the main entrance examinations, such as the National High School Exam - ENEM, but also progress in learning of complex content through its motivating, playful and interactive character. In addition, the using of comics  in the learning promote the reinvention of teaching practices by teachers to take advantage of the potential that only comics provide.We used a qualitative methodology of a descriptive nature that resulted in the construction of this didactic proposal that will initially be worked on in the project.The project “Only the Basic” comes exactly to promote initial provocations to mobilize students' previous knowledge, putting into practice a new proposal with the use of comics.So our study proposes teachers a practical handbook to guide them in their educational practices in times of pandemic, in order to familiarize them with the resource of comics, being able to adapt them to meet their goals, time and audience.